1993
DOI: 10.1042/bj2930109
|View full text |Cite
|
Sign up to set email alerts
|

Activation of phospholipase A2 and stimulation of prostaglandin E2 production by transforming growth factor-α in rat thymic epithelial cells requires influx of calcium

Abstract: The stimulation of both phospholipase A2 (PLA2) enzymic activity and the production of prostaglandin E2 (PGE2) by transforming growth factor-alpha (TGF-alpha) and Ca2+ ionophore A23187 in TEA3A1 rat thymic epithelial cells were studied. TGF-alpha by itself at various concentrations (5-200 ng/ml) had no effect on the stimulation of PGE2 production. A23187 (1 microgram/ml) by itself stimulated PGE2 production on average by 18-fold over the control. When TGF-alpha (50 ng/ml) was added to the cells in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…This result is consistent with previous studies that EGF caused [ 3 H]-AA release in human mesangial cells and rat mesangial cells in culture [45]. Activation of PLA 2 and subsequent stimulation of PGE 2 production requires the activation of EGF receptor tyrosine kinase and Ca 2+ influx in rat thymic epithelial cells [46]. In primary cultures of rabbit PTCs, EGF increases 5,6-EET, a major metabolite of cytochrome P-450 epoxygen-ase, which induces Ca 2+ influx [47].…”
Section: Discussionsupporting
confidence: 82%
“…This result is consistent with previous studies that EGF caused [ 3 H]-AA release in human mesangial cells and rat mesangial cells in culture [45]. Activation of PLA 2 and subsequent stimulation of PGE 2 production requires the activation of EGF receptor tyrosine kinase and Ca 2+ influx in rat thymic epithelial cells [46]. In primary cultures of rabbit PTCs, EGF increases 5,6-EET, a major metabolite of cytochrome P-450 epoxygen-ase, which induces Ca 2+ influx [47].…”
Section: Discussionsupporting
confidence: 82%
“…TGF‐α and EGFR are critical modulators of cytokine production from human and mouse TEC and therefore they can regulate thymocyte proliferation and development 21, 28–30. Previous studies showed a causal relationship between the EGFR stimulation and subsequent PGE 2 release from TEC‐derived cell lines or TEC primary cultures from rodents 30, 31, although the COX isozyme accounting for PGE 2 release was not specified. On the other hand, it is known that EGFR enhances COX‐2‐dependent PGE 2 synthesis in many mammalian epithelial cells other than TEC, such as normal human epidermal keratinocytes 32, human bronchial epithelial cells 33, human squamous carcinoma cell lines 32.…”
Section: Discussionmentioning
confidence: 99%
“…During this early period, the number of lamina propria lymphocytes also increases and changes occur in the subsets of resident R and T lymphocytes [Rothkotter, 1991], EGF and TGFa have been implicated in thymus development [Andersen et al. 1993] and in stim ulation of cytokine [review: Le and Singer, 1993] and prostaglandin [Liu et al, 1993] production in thymic ep ithelial cells; the possibility that TGFa is involved in the maturation and function of developing lymphoid tissue in suckling pigs is intriguing.…”
Section: Discussionmentioning
confidence: 99%